2020
DOI: 10.1021/acsami.9b18357
|View full text |Cite
|
Sign up to set email alerts
|

Maximizing Short Circuit Current Density and Open Circuit Voltage in Oxygen Vacancy-Controlled Bi1–xCaxFe1–yTiyO3−δ Thin-Film Solar Cells

Abstract: Designing solid-state perovskite oxide solar cells with large short circuit current (J SC ) and open circuit voltage (V OC ) has been a challenging problem. Epitaxial BiFeO 3 (BFO) films are known to exhibit large V OC (>50 V). However, they exhibit low J SC (≪μA/cm 2 ) under 1 Sun illumination. In this work, taking polycrystalline BiFeO 3 thin films, we demonstrate that oxygen vacancies (V O ) present within the lattice and at grain boundary (GB) can explicitly be controlled to achieve high J SC and V OC simu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…However, the mixing of the R3c phase along with slight tetragonal symmetry could affect small changes in V oc of the Al/NBFNT75/Ag system based on the reduction of symmetry breaking mechanism. [23] The results of this study demonstrated that the measured short-circuit current density increases linearly with reduced bandgap, as shown in Table 4. By increasing metal content, the absorption edge was shifted to higher wavelength regions (Figure S6, Supporting Information), indicating a wider range of solar absorption and thus enhancing PV efficiency.…”
Section: Fe Photovoltaicmentioning
confidence: 52%
See 2 more Smart Citations
“…However, the mixing of the R3c phase along with slight tetragonal symmetry could affect small changes in V oc of the Al/NBFNT75/Ag system based on the reduction of symmetry breaking mechanism. [23] The results of this study demonstrated that the measured short-circuit current density increases linearly with reduced bandgap, as shown in Table 4. By increasing metal content, the absorption edge was shifted to higher wavelength regions (Figure S6, Supporting Information), indicating a wider range of solar absorption and thus enhancing PV efficiency.…”
Section: Fe Photovoltaicmentioning
confidence: 52%
“…When a bulk PV device is illuminated with light, charge carriers are introduced at the metal/FE/metal interface. [ 23,24 ] The work function difference between the two metal electrodes ( φ Al = 4.125 eV and φ Ag = 4.28 eV) creates an asymmetric charge accumulation at both interfaces, generating a built‐in electric field that separates the photogenerated charge carriers and produces a large open‐circuit voltage. [ 23 ] However, according to Nandy et al, maximum Vo¨$\overset{\cdot\cdot}{\text{o}}$ and large V oc cannot exist in the same system.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the most popular materials in modern micro-and nanoelectronics is monocrystalline silicon and silicon dioxide [1,2]. Recently, thanks to the creation of quantum-dimensional structures on silicon [3][4][5], the di culty of using the above materials in photoelectronics, due to their low probability of radiative recombination, has been overcome [6][7]; thus, a new impetus has been obtained for its widespread use in the aforementioned elds of science and technology [8]. In the production of silicon integrated circuits, in addition to the quality of the surface structure, the choice of the crystallographic orientation of the substrate crystals is of great importance [9][10][11]; for example, the (111) planes are oxidized faster than the (100) planes due to the high surface packing density of atoms capable of entering the oxidation reaction [12].…”
Section: Introductionmentioning
confidence: 99%
“…With delicate dopings, open-circuit voltages were claimed to be tuned from 0.5–3 to 3–8 V. However, the reported data support an average voltage of 6 V with a widely dispersed voltage from 3 to 8 V, in which the highest voltage is claimed as the top voltage in the literature. Remarkable efficiencies of 0.11–0.22% were recorded for FTO/Bi 0.8 Ca 0.2 FeO 3−δ /Au cells with open-circuit voltages from 0.1 to 0.3 V and current densities of ∼2.6 to 3.2 mA·cm –2 . Although the enhanced ferroelectric properties account for the high voltage on doped BFO samples, the varied current and voltage on a definite component are vague, reflecting the uncertainty about the nature of the reported above-band-gap voltages.…”
Section: Introductionmentioning
confidence: 99%